Mountainous grasslands sustaining traditional livestock systems: The economic performance of sheep and goat transhumance in Greece - Ragkos A.; Siasiou A.; Galanopoulos K.; Lagka V. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
This study presents the economic performance of transhumant farms, by taking into account two crucial factors: farm size and environmental impact. The analysis is based on technical end economic data from a sample of 121 transhumant farms from Greece which move towards a wide range of summer pasturelands. The farms were grouped according to number of reared animals, thus formulating three groups: <350 animals, 351-600 animals and >600 animals. Economic results and technical and economic indicators have been calculated for each group in order to investigate potential differences stemming from farm size. There are two main findings from the analysis, the first relating to the role of farm size in the economic performance and the second to interactions between economic performance and environmental protection. Indeed, the relationship between transhumance and the environment is two-fold: transhumant flocks contribute to the protection of natural mountainous grasslands and the use of these grasslands becomes an important factor in sustaining their economic viability.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)